Synergistic growth-inhibitory effects of ponatinib and midostaurin (PKC412) on neoplastic mast cells carrying KIT D816V - Karoline V. Gleixner; Barbara Peter; Katharina Blatt; Verena Suppan; Andreas Reiter; Deepti Radia; Emir Hadzijusufovic; Peter Valent (Haematologica, 2013)
Patients with advanced systemic mastocytosis, including mast cell leukemia, have a poor prognosis. In these patients, neoplastic mast cells usually harbor the KIT mutant D816V that confers resistance against tyrosine kinase inhibitors. We examined the effects of the multi-kinase blocker ponatinib on neoplastic mast cells and investigated whether ponatinib acts synergistically with other antineoplastic drugs. Ponatinib was found to inhibit the kinase activity of KIT G560V and KIT D816V in the human mast cell leukemia cell line HMC-1. In addition, ponatinib was found to block Lyn- and STAT5 activity in neoplastic mast cells. Ponatinib induced growth inhibition and apoptosis in HMC-1.1 cells (KIT G560V+) and HMC-1.2 cells (KIT G560V+/KIT D816V+) as well as in primary neoplastic mast cells. The effects of ponatinib were dose-dependent, but higher IC50-values were obtained in HMC-1 cells harboring KIT D816V than in those lacking KIT D816V. In drug combination experiments, ponatinib was found to synergize with midostaurin in producing growth inhibition and apoptosis in HMC-1 cells and primary neoplastic mast cells. The ponatinib+midostaurin combination induced substantial inhibition of KIT-, Lyn-, and STAT5 activity, but did not suppress Btk. We then applied a Btk short interfering RNA and found that Btk knockdown sensitizes HMC-1 cells against ponatinib. Finally, we were able to show that ponatinib synergizes with the Btk-targeting drug dasatinib to produce growth inhibition in HMC-1 cells. In conclusion, ponatinib exerts major growth-inhibitory effects on neoplastic mast cells in advanced systemic mastocytosis and synergizes with midostaurin and dasatinib in inducing growth arrest in neoplastic mast cells.